Epigenetic Regulation and Measurement of Epigenetic Changes. (October 2013) - Stephens, Kimberly E.; Miaskowski, Christine A.; Levine, Jon D.; Pullinger, Clive R.; Aouizerat, Bradley E.
Epigenetic mechanisms provide an adaptive layer of control in the regulation of gene expression that enables an organism to adjust to a changing environment. Epigenetic regulation increases the functional complexity of deoxyribonucleic acid (DNA) by altering chromatin structure, nuclear organization, and transcript stability. These changes may additively or synergistically influence gene expression and result in long-term molecular and functional consequences independent of the DNA sequence that may ultimately define an individual's phenotype. This article (1) describes histone modification, DNA methylation, and expression of small noncoding RNA species; (2) reviews the most common methods used to measure these epigenetic changes; and (3) presents factors that need to be considered when choosing a specific tissue to evaluate for epigenetic changes.